Diagnóstico sanitario (parasitario) en ovinos marin magellan meat merino (4m) en el núcleo genético Yanahurco de la provincia de Cotopaxi. - Nacimba Topón, Paulina Elizabeth (2020)
The objective of this research was to carry out the sanitary (parasitic) diagnosis in Marin Magellan Meat Merino (4M) sheep in the Yanahurco genetic nucleus of the Cotopaxi province, located in the Saquisilí canton in which a population of 60 sheep was analyzed from Stool samples through coprological examinations using the helminth-ovoscopic flotation method of Faust, in which the percentage of positive animals was determined, percentage distribution according to the genus of identified parasites, age, sex and the species of parasite with greater prevalence at each stage. Descriptive statistics were used analyzing the maximum values, minimum values , and percentages through the Excel 2016 program. Of the results obtained from the 60 fecal samples of the animals examined, all 36 sheep, that is, 60%, were positive for some helminth infestation of the Nematoda class. The most relevant genera in all animals according to the parasitic species were: Nematodirus spp. 50%, Haemonchus spp. 22%, Tenia spp. 13% About age, sheep (3-4 months, 1 year, 5 years) are evaluated, it is evident that 5-year-old animals have 53% parasitosis, which is parasitized with three spices Taenia spp. 66%, Nematodirus spp. 33%, Haemonchus spp. 16%, concerning the relationship according to sex, a higher percentage of parasitosis in females was found with 35% of which were found to have an incidence of the following genera, Haemonchus spp. 84%, Coccidias spp. 67%, Nematodirus spp. 49%, Taenia spp. 66%, Trichuris spp. 67% Under the conditions of the present study, a high percentage of parasitized sheep on this farm is concluded.